Body mass index and endometriosis: Is there a relationship?. Issue 2 (June 2022) - Arablou, Tahereh; Khodaverdi, Sepideh; Kolahdouz-Mohammadi, Roya; Farhangnia, Pooya; Delbandi, Ali-Akbar
Objective: Previous studies on the relationship between the presence of endometriosis (EM) and body mass index (BMI) have shown inconsistent results. This study aimed to compare the BMI between women with EM and non-endometriotic controls. Methods: In the present cross-sectional study, BMI of 65 endometriotic women with 43 non-endometriotic controls undergoing laparoscopy were compared. The comparison of BMI between the two groups and in disease stages was analyzed using t -test. Results: BMI was significantly lower in women with EM compared to control women ( p  = 0.01). There were no statistically significant differences in BMI between disease stages. Conclusion: The present study results showed that women with EM have lower BMI compared to non-endometriotic controls. More studies are suggested to clarify the mechanisms of this association.